Analyzing users' performance interacting with a digitized traditional game on multi-touch display using fitts's law - Mahamad, S. (Universiti Teknikal Malaysia Melaka, 2018)
This paper presents an analysis of digitalizing traditional games by using multi-touch digital tabletop through Fitts's law. The objectives of this paper are to study the accuracy of the user aiming performance using the Fitts's Law towards the application, and to determine the movement time with different index of difficulty of the application. Besides, it's to determine the appropriate size of the shooter marble and the target marble for the game design on the multi touch digital tabletop based on traditional games. The development encourage the collaborative works among the children to communicate with each other for increasing their social skills. The conducted experiment concludes the suitable size of the object in the application with the size of tabletop in guiding the user interface (UI) development. Â© 2018 Universiti Teknikal Malaysia Melaka. All rights reserved.